Faktor-Faktor Yang Mempengaruhi Produksi Jeruk Nipis (Citrus Aurantifolia) di Desa Sei Litur Kecamatan Sawit Seberang Kabupaten Langkat - A.P., Ginting; Hanisah; Rozalina (Jurnal Penelitian Agrisamudra, 2024)
This research aims to analyze the factors that influence lime production (Citrus aurantifolia) in Sei Litur Tasik Village, Sawit Seberang District, Langkat Regency. The sampling technique used was nonprobability sampling. The number of samples in this research was 31 lime farmers in Sei Litur Tasik Village, Sawit Seberang District, Langkat Regency. The type of nonprobability sampling used is saturated sampling. The data used in the research are primary data and secondary data. To find out what factors influence lime production in Sei Litur Tasik Village, Sawit Seberang District, Langkat Regency, statistical analysis using the multiple linear regression method was used. Data processing was carried out using SPSS software version 25. The results of this study show that farming experience and number of plants have a significant influence on lime production in Sei Litur Tasik Village, Sawit Seberang District, Langkat Regency and the variables of land area and plant age have no effect on orange production. thin in Sei Litur Tasik Village, Sawit Seberang District, Langkat Regency.